2015
DOI: 10.1007/s00586-015-4010-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of morbidity and mortality among patients with cervical spondylotic myelopathy treated surgically

Abstract: The NIS database was used to provide national estimates of morbidity and mortality following surgical management of CSM in the United States. Several comorbidities, as well as demographic and surgical parameters, were identified as associated factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 24 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…In addition to obesity, weight loss has also been shown to affect surgical prognosis; ‘pathological weight loss’, defined as greater than 10% of body weight within 6 months of surgery, has been shown to be a predictor of 30-day hospital readmission in patients undergoing PCF. 41 Similarly, pathological weight loss was found to significantly increase surgical mortality rate, 40 and to be a significant predictor of aspiration. 42 …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition to obesity, weight loss has also been shown to affect surgical prognosis; ‘pathological weight loss’, defined as greater than 10% of body weight within 6 months of surgery, has been shown to be a predictor of 30-day hospital readmission in patients undergoing PCF. 41 Similarly, pathological weight loss was found to significantly increase surgical mortality rate, 40 and to be a significant predictor of aspiration. 42 …”
Section: Resultsmentioning
confidence: 94%
“…On the contrary, 1 study reported that obesity was associated with a decreased risk of mortality and a higher functional independence in surgical DCM patients. 40 Another study reported greater mental-state-improvement post-operatively in obese patients. 31 Other studies found that both mental and physical improvements were poorer in obese patients compared to non-obese patients after anterior cervical surgery.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[24] Private insurance status was found to be a predictor of anterior cervical fusions for the treatment of CSM, which was also found to be the approach with the lowest mortality. [416] The increased use of fusion surgery in patients with private insurance could be explained by the increased rate of collection of hospital charges from private payers in comparison to Medicare/Medicaid. [18]…”
Section: Discussionmentioning
confidence: 99%
“…[12] Another recent study indicated that posterior-only approaches are associated with a higher rate if mortality, which might also explain the decreased utilization of posterior approaches as compared to anterior fusions. [4]…”
Section: Discussionmentioning
confidence: 99%